IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY THROUGH PICTIONARY GAME OF SD NEGERI 05 PONTIANAK TIMUR - Erni, .; Sada, Clarry; Supardi., Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This study discussed about using pictionary game to improve studentsâ€™ vocabulary mastery to the third grade students of SDN 05 Pontianak Timur. The data were gathered from classroom observations and interview. The analysis showed how Pictionary game gave an improvement in pronouncing, knowing and memorizing words. It provided opportunities for students to improve the vocabulary mastery as well as motivation to help the teacher managing classroom interaction. It also enabled the students to experience the vocabulary; they made noticeable progress in their vocabulary learning, gaining the confidence to pronounce word in pronouncing. In short, this study showed that Pictionary game promoted students active participation in the activities with more opportunities to improve their vocabulary through practice which in turn increased their positive attitude for language learning. Â Key words: Pictionary Game, improving, pronouncing, knowing, memorizing, mastery, vocabulary, English language. Abstrak: Penelitian ini membahas tentang pengunaan Pictionary game untuk mengembangkan penguasaan kosakata terhadap siswa-siswa kelas tiga SDN 05 Pontianak Timur. Data diperoleh dari observasi kelas dan wawancara. Hasil analisis menunjukkan bahwa Pictionary game memberikan perbaikan dalam pengucapan, pengetahuan dan pengingatan kata-kata. Adanya kesempatan untuk para siswa untuk mengembangkan penguasaan kosakata serta motivasi dapat membantu guru mengelola interaksi kelas. Hal ini juga memungkinkan siswa untuk berpengalaman dalam berkosakata; mereka membuat kemajuan yang nyata dalam belajar kosakata, memperoleh kepercayaan diri untuk menyebutkan kata dalam pengucapan. Singkatnya, penelitian ini menunjukkan bahwa Pictionary game menumbuhkan keaktifan partisipasi siswa dalam kegiatan dengan kesempatan mengembangkan kosakata mereka melalui praktek yang meningkatkan sikap positif mereka dalam belajar bahasa. Kata kunci: Pictionary Game, mengembangkan, pengucapan, pengetahuan, pengingatan, penguasaan kosakata, bahasa Inggris